Relevansi Ayat-Ayat Politik Al-Qur’an dalam Tata Kelola Pemerintahan Modern: Kajian Kualitatif Tafsir Tematik: Penelitian - M Habib Alhabsyi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In the comprehensive understanding of Islam, the political aspect has a crucial position in regulating the life of the community as a whole, including the social, legal, economic, and government administration fields. The Qur'an contains many verses that explicitly or implicitly discuss various topics related to power, leadership, justice, responsibility, and deliberation. These verses are known as political verses because they contain fundamental. principles in establishing an ethical and responsible system of government. This study aims to examine the relationship of political verses in the Qur'an to the principles of modern governance with a qualitative research approach and using the thematic interpretation method. The findings show that the political values listed in the Qur'an, such as justice, trust, deliberation, as well as competency-based leadership, are in line with the principles of good governance consisting of accountability, participation, transparency, and the rule of law. Through contextual and integrative interpretation, political verses in the Qur'an can make a meaningful contribution in formulating a more just, participatory, and civilized governance model.